Selfassessment of General Practitioners Graduated from Kerman University of Medical Sciences Iran in Competency to Diagnose and Treat Orthopedic Problems - Ali Poor Amiri; Ghodsieh Khalili; Mostafa Shokoohi (Kerman University of Medical Sciences, 2013)
Background & Objective: Evaluating students ability in diagnosing and treating patients after graduation has been recognized as a priority for medical education The aim of this study is to evaluate students ability after graduation from Kerman University of Medical Sciences Iran in diagnosing and treating orthopedic problems Methods: This is a retrospective cross sectional study carried out on 115 graduated general practitioners of 20012006 academic year In this study to evaluate the competency of general practitioners graduated from KUMS in musculoskeletal medicine participants were asked to complete a standard questionnaire with 36 questions in 9 domains Results: The total competency of the studied people was 65% The highest competency level was related to the domains of treatment of fractures and dislocation the initial treatment of open fractures and diagnosis of fracture and dislocation (80% 77% and 73% respectively) The lowest competency level was related to the domains of congenital deformity of feet musculoskeletal system tumors and congenital dislocation of the hip (47% 50% and 52% respectively) No difference was observed between men and women in the mentioned domains Conclusion: The results of our study revealed that in general the competency of graduated physicians was average Accordingly it is recommended that universities recognize weaknesses of graduated general practitioners according to a compiled program Moreover annual education programs can prevent more problems from occurring in the work setting and higher levels of education of these general practitioners